Ag Functionalized In2O3 Derived From MIL-68(In) as an Efficient Electrochemical Glucose Sensor - Arif, Dooa; Hussain, Zakir; Abbasi, Amna Didar; Sohail, Manzar (Frontiers in Chemistry, 2022)
In this study, Ag@In2O3 modified nickel foam (NF) was reported for its role as a non-enzymatic glucose sensor. Ag@In2O3 was prepared by a simple two-step method; preparation of a metal-organic framework (MOF) MIL-68(In) by solvothermal method, entrapment of Ag+ by adding AgNO3 followed by drying for 2 h to complete the entrapment process and subsequent calcination at 650 ºC for 3 h. The Ag@In2O3 modified NF was employed as a non-enzymatic glucose sensor to determine glucose concentrations in an alkaline medium. Two linear ranges were obtained from Ag@In2O3 modified electrode, i.e. 10 µM to 0.8 mM and 0.8 mM to 2.16 mM with a sensitivity of 3.31 mA mM-1 cm-2 and 1.51 mA mM-1 cm-2 respectively, with a detection limit of 0.49 µM. Ag@In2O3 modified NF exhibited high selectivity for glucose, among other interfering agents.